Aplicación del método de wirtinger para la gestión óptima de recursos en una red eléctrica de distribución. - Gómez Coro, Robinson Alexander (2023)
The purpose of this work is to implement an optimization model based on convexity, which is based on the method proposed by Wilhem Wirtinger, a calculation that is responsible for analyzing analytic and non-analytic functions in the plane of complex numbers and then defines new operators called Wirtinger derivatives, they allow to generate new approximations to linear equations that are directly coupled in the development of problems with power flows, differentiating from other traditional methods, which use non-linear equations and therefore do not allow a global solution either. . The linearization described is introduced through the study of optimal power flows and are used in cases of minimization of energy costs, which are subject to restrictions on the availability of distributed resources that allow satisfying the demand.